Study the Potential of Tangible and Intangible Folk Heritage in Promoting Tourism in Yamuna River Basin of Garhwal Himalayan Region (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In order to develop sustainable tourism in the Yamuna River Basin of the Garhwal Himalayan area, this research explores the possibility of using both physical and intangible cultural heritage. Architectural wonders, traditional crafts, oral traditions, performing arts, and celebratory events are all part of the region's rich cultural fabric, which is explored via qualitative analysis of secondary data sources. The study's overarching goal is to inform policymakers and practitioners on how to best promote culturally sensitive tourism that creates jobs and protects local traditions without compromising the integrity of historic sites.